On the Selective Relation of Frontal Cortical Asymmetry and Anger-Out Versus Anger-Control. (article). - Hewig, Johannes
The model of anterior asymmetry and emotion purposes and asymmetry representations of approach and withdrawal system in the left and right anterior brain regions. Within this framework, 3 different concepts have been related to anterior asymmetry : affective valence, motivational direction, and behavioral activation. The aim of the present study was an empirical investigations into the relation between anterior cortical activity and questionnaire measures related to the 3 dimensions positive versus negative affect, approach versus withdrawal motivation, and behavioral activation versus inhibition. Subjects with relative greater left than right frontal cortical activity showed higher anger-out scores and lower anger-control scores. These results support hypothesis that motivational direction is related to frontal asymmetry (approach-left and withdrawal -right). Furthermore, subjects with greater bilateral ( left and right) frontal cortical activity showed behavioral activation scores. This finding might suggest that behavioral activation is related to approach and withdrawal motivation. -- (from the author)
Keywords: Psychology-Periodicals.